Wymiar wschodni Unii Europejskiej – komplementarny czy konkurencyjny dla pozostałych kierunków polityki zagranicznej Unii? (analogie i rozbieżności) - Piskorska, Beata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
Although Eastern Partnership has won the support of the EU Member States it remains an initiative competitive for the Mediterranean Union, which is strongly promoted by France. Eastern policy can distract the EU’s attention from the issue of North Africa France places so much importance on, therefore France can be expected to tend to marginalize the significance of Eastern Partnership. The same attitude may also be supported by Russia (as France attempts to establish cooperation along the Paris–Berlin–Moscow line, while neglecting the interests of Poland and Central and Eastern European countries).